THE EFFECTS OF CHILD LABOR EXPLOITATION AS REFLECTED IN ELIZABETH BARRETT BROWNING’S “THE CRY OF THE CHILDREN” - Jati, Bella Amanda (LANTERN (Journal on English Language, Culture and Literature), 2014)
Elizabeth Barrett Browning’s “The Cry of the Children” is one of many poems which portray the condition of child labors in Victorian Era. The objectives of this thesis are to show that child labor exploitation really happens through intrinsic elements, to describe the conditions of the child labors, and to explain several effects of child labor exploitation in Victorian Era. The writer uses library research in collecting the data. To analyze the extrinsic elements of the poem, the writer uses sociological criticism. The result of this thesis is that the exploitation gives several effects to the child labors. It is represented by the child labors’ wish for death, the loss of happiness as children, and the skepticism towards God. It can be concluded that children should have freedom so they can feel love and happiness.